2019
DOI: 10.4110/in.2019.19.e4
|View full text |Cite
|
Sign up to set email alerts
|

Potential Implications of Long Noncoding RNAs in Autoimmune Diseases

Abstract: Long noncoding RNAs (lncRNAs) are non-protein coding RNAs of more than 200 nucleotides in length. Despite the term “noncoding”, lncRNAs have been reported to be involved in gene expression. Accumulating evidence suggests that lncRNAs play crucial roles in the regulation of immune system and the development of autoimmunity. lncRNAs are expressed in various immune cells including T lymphocytes, B lymphocytes, macrophages, neutrophils, dendritic cells, and NK cells, and are also involved in the differentiation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 86 publications
(106 reference statements)
1
49
0
1
Order By: Relevance
“…However, the majority of studies so far have focused on coding genes, particularly the function of cell-surface receptors, cytokines, and transcription factors. Recently, increasing evidence has revealed that lncRNAs can play fundamental roles in the regulation of the immune system 8,9 . For example, the lncRNA NeST has been found to be related with T-cell activation and to be critical for immune response regulation 10 .…”
mentioning
confidence: 99%
“…However, the majority of studies so far have focused on coding genes, particularly the function of cell-surface receptors, cytokines, and transcription factors. Recently, increasing evidence has revealed that lncRNAs can play fundamental roles in the regulation of the immune system 8,9 . For example, the lncRNA NeST has been found to be related with T-cell activation and to be critical for immune response regulation 10 .…”
mentioning
confidence: 99%
“…With the development of high-throughput gene sequencing technology, numerous lncRNAs have been identified and demonstrated to exert biological functions through interactions with other cellular macromolecules (28). LncRNAs are expressed in various types of immune cells and participate in the differentiation and activation of these cells (29). RA is an autoimmune disorder, with CD4 + T cells differentiating into various Th-cell subsets that are thought to be deeply involved in the pathogenesis of RA (30).…”
Section: Discussionmentioning
confidence: 99%
“…lncRNAs are involved in the regulation of gene expression, cell proliferation, differentiation, and immune response [62]. Recent studies have highlighted the essential role of lncRNAs in immune responses and suggested that lncRNAs are involved in the development of autoimmune diseases [63][64][65][66]. lncRNAs modulate different cytokines (e.g., IL-6 or TNF-α) in immune cells during the pathogenesis of RA [67].…”
Section: Long Noncoding Rnasmentioning
confidence: 99%